Pengaruh Kontrol Diri Dan Diskon Terhadap Impulse Buying Pada Generasi Z Pengguna Aplikasi TikTok Shop Di Kabupaten Kolaka - Selfiana Selfiana; Andry Stepahnie Titing; Ismanto Ismanto (STIKes Ibnu Sina Ajibarang, 2023)
This study aims to determine: (1) the effect of self-control on impulse buying in generation Z titkok shop application users in kolaka regency. This research is an explanatory research model with a quantitative approach. data collection in this study used observation, documentation and questionnaire distribution. The population in this study are all generation z comsumers who use the tiktok shop application in kolaka regency. While the population in this study amounted to 120 respondents using purposive sampling technique, namely sampling techniques with certain criteria. This research instrument test uses validity and reliability tests with SPSS 25.0. The data analysis technique used in this research is structural equation modeling (SEM) based on partial least square (PLS) with measurement model testing (outer model) and structural model testing (inner model) with smart PLA 4.0. Based on the result of the study, it is known tht there is a negative and significant influence between self-control variables on impulse buying, this is indicated by a P-Value of 0.039. and the discount variable has a positive and significant effect on impulse buying, this is indicated by a p-value of 0.000.